Recent Advances in Liver Cancer Stem Cells: Non-coding RNAs, Oncogenes and Oncoproteins - Li, Juan; Zhu, Ying (Frontiers in Cell and Developmental Biology, 2020)
Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies worldwide, with high morbidity, relapse, metastasis and mortality rates. Although liver surgical resection, transplantation, chemotherapy, radiotherapy and some molecular targeted therapeutics may prolong the survival of HCC patients to a certain degree, the curative effect is still poor, primarily because of tumor recurrence and the drug resistance of HCC cells. Liver cancer stem cells (LCSCs), also known as liver tumor-initiating cells, represent one small subset of cancer cells that are responsible for disease recurrence, drug resistance and death. Therefore, understanding the regulatory mechanism of LCSCs in HCC is of vital importance. Thus, new studies that present gene regulation strategies to control LCSC differentiation and replication are under development. In this review, we provide an update on the latest advances in experimental studies on non-coding RNAs (ncRNAs), oncogenes and oncoproteins. All the articles addressed the crosstalk between different ncRNAs, oncogenes and oncoproteins, as well as their upstream and downstream products targeting LCSCs. In this review, we summarize three pathways, the Wnt/β-catenin signaling pathway, phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway, and interleukin 6/Janus kinase 2/signal transducer and activator of transcription 3 (IL6/JAK2/STAT3) signaling pathway, and their targeting gene, c-Myc. Furthermore, we conclude that octamer 4 (OCT4) and Nanog are two important functional genes that play a pivotal role in LCSC regulation and HCC prognosis.